Carbon Dioxide Adsorption Equilibrium Rates Comparative Temperature Study Using Palm Kernel Shell Sorbent. Issue 1 (June 2020) - Sahri, Dzulkarnain Mohd; Zaini, Nabilah; Nasri, Noor Shawal; Zain, Husna Mohd; Rashid, Norhana Mohamed; Noor Shawal, Anis Shahirah
Abstract: Greenhouse effect is the serious environmental issue whereby the gaseous component involved is dangerous. One of the gases that contributed to atmosphere is carbon dioxide (CO2 ), in which is more than 80%, followed by methane and nitrous oxide that resulted from human activities, industrial sector and transportation. Activated carbon (AC) is the best adsorption technology due to simple design and ability to capture carbon dioxide efficiently. This paper was aimed to produce activated carbon derived from waste material, to determine adsorption rate at different pressures and temperatures and to relate adsorption kinetics and isotherms equilibrium to describe adsorption processes. Palm Kernel Shell (PKS) was selected as raw material to produce AC. Char was produced via carbonization process at 700 °C ± 20 °C for 2 h with 10 °C/min heating rate under inert gas flow. The sample is then grinded and sieved to 0.65mm to 0.8mm, followed by chemical treatment by using potassium hydroxide with ratio of 1:1 and directly undergoing microwave treatment. Adsorption rate performances were investigated by different temperatures of 25 °C and 10 °C and pressures of 5, 15 and 25 bar. The sample were characterized by thermo-gravimetric analysis, surface area analysis, and ultimate analysis. AC-PKS shows the highest surface area. As a result, increase in pressure led to increase in CO2 adsorption while decrease in temperature in CO2 adsorption. In conclusion, the findings revealed that the potential of AC-PKS to capture CO2 in order to enhance environmental sustainability and economically.